Social program and digital marketing strategy in community development projects in MSME “Sodagar Snack” at Kuningan, East Java - Prasetya, Prita; Polla, Denzel Da; Santosa, Derick Philander; Wijaya, Gabriella Aurielle; Suharto, Khantidhira Winona; Rifki, Mohammad; Hajadi, Stefanus Jason; Latuperisa, Stelya Clarence; Novesaria, Veronica Lila (Priviet Social Sciences Journal, 2023)
Digitalization has become essential in developing businesses, including Micro, Small, and Medium Enterprises (MSMEs). Community Development program was held in Kuningan, Groupst Java whose focus was on MSMEs, "Sodagar Snack." This activity aims to increase awareness of the importance of digitalization in MSME business, introduce marketing applications, facilitate capital, and sustainably encourage the digitalization of   MSME bisnis. Implementing this service involves interaction with MSMEs, "Sodagar Snack," socialization, training, and developing entrepreneurship and Dukcapil programs. The results found during this service activity are that MSMEs "Sodagar Snack" still have minimal knowledge and awareness of essential business activities. The expected outcomes of community service activities are MSME actors gaining additional knowledge about the potential for business digitalization, expanding business networks for collaboration with local  MSMEs, and helping improve the economy of  MSMEs in Kuningan, East Java.